2001
DOI: 10.1159/000048633
|View full text |Cite
|
Sign up to set email alerts
|

Age- and Dementia-Associated Impairments in Divided Attention: Psychological Constructs, Animal Models, and Underlying Neuronal Mechanisms

Abstract: Following a brief description of the psychological construct ‘divided attention’, impairments in divided attention and related executive functions are discussed as the major variable in the development and manifestation of age- and dementia-associated cognitive impairments. Neuropsychological and functional imaging studies in humans have indicated that dorsolateral and ventrolateral prefrontal, cingulate, parietal and premotor cortical areas are involved in the mediation of dual task performance. Furthermore, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
23
0

Year Published

2002
2002
2014
2014

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(24 citation statements)
references
References 150 publications
(142 reference statements)
1
23
0
Order By: Relevance
“…In addition, a study of cholinergic lesions in marmosets demonstrated that, when hippocampal inputs alone are interrupted, monkeys could perform simple visual discriminations but not conditional visuospatial discriminations (Ridley et al, 1999). Recent data also suggest that the cholinergic system and performance of prefrontal cortexassociated executive functions may be one locus of interaction (reviewed in Robbins, 2000;Sarter and Turchi, 2002), and further studies are necessary to dissociate the role of cortical versus hippocampal cholinergic input on relational memory. Viewed together, these results suggest that cholinergic input to the hippocampus plays a significant modulatory role on complex hippocampal information processing.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, a study of cholinergic lesions in marmosets demonstrated that, when hippocampal inputs alone are interrupted, monkeys could perform simple visual discriminations but not conditional visuospatial discriminations (Ridley et al, 1999). Recent data also suggest that the cholinergic system and performance of prefrontal cortexassociated executive functions may be one locus of interaction (reviewed in Robbins, 2000;Sarter and Turchi, 2002), and further studies are necessary to dissociate the role of cortical versus hippocampal cholinergic input on relational memory. Viewed together, these results suggest that cholinergic input to the hippocampus plays a significant modulatory role on complex hippocampal information processing.…”
Section: Discussionmentioning
confidence: 99%
“…Impairments in the ability to divide attention, as typically assessed by dual task performance, are generally correlated with chronological age (Crossley and Hiscock, 1992; Salthouse et al, 1995; for review see Sarter and Turchi, 2002). This main effect of age is typically interpreted as reflecting a decrease in the overall capacity for information processing or a decline in the executive management of such resources (Craik et al, 2010; Tombu and Jolicæeur, 2003).…”
Section: Aging and Pd-associated Impairments In Attention And Loss Ofmentioning
confidence: 99%
“…Impairment of executive function results in difficulties with activities of daily living, such as making a meal that might involve sequentially and flexibly washing, cutting, and boiling food (Carlson et al, 1999). Executive function is known to decrease with age (Cepeda et al, 2001;Verhaeghen and Cerella, 2002), and most dementia patients (Dishman et al, 2006;Sarter and Turchi, 2002) show impaired executive function. In recent years, physical exercise has been considered to contribute to the prevention of decrease in executive function in the elderly Kramer et al, 2003;McAuley et al, 2004).…”
Section: Introductionmentioning
confidence: 99%